Application of self-determination theory on the motivation structure of hotel management employees - Stanisic, Natasa; Čerović, Slobodan (Serbian Journal of Management, 2021)
Self-determination theory that was used as a starting point of this paper, indicates the existence of different types of motivation that are distributed along the motivational continuum and which differ according to the degree of self-determination, the formation of which is under the influence of the environmental and individual factors. This research presents the applicability of the basic postulates of self-determination theory on a sample of 150 employees within the hotel sector in Belgrade. The aim of this paper is to determine the extent of which environmental factors, such as work climate, affect the satisfaction of basic psychological needs of employees and through them, the structure of motivation (autonomous/controlled/amotivation). The results of this research show that the work climate, which is defined as perceived autonomy support, significantly affects the satisfaction of psychological needs and motivation for work, where the satisfaction of basic psychological needs has a mediating role, thus creating conditions for developing autonomous forms of motivation.
Keywords: basic psychological needs; autonomous motivation; controlled motivation; amotivation; work motivation